PELAKSANAAN SYSTEM DAN PROSEDUR ADMINISTRASI PERCERAIAN DI KABUPATEN PELALAWAN - Reni Pebrina (Badan Penelitian dan Pengembangan Daerah Kab. Pelalawan, 2023)
This paper examines the implementation of the divorce administration system and procedures in Pelalawan Regency, with a focus on civil servants. The research is based on government regulations that require permission from authorized officials for civil servants to obtain a divorce. The study finds that there are still some shortcomings in the current administrative procedures for divorce, which are carried out manually. The research suggests that there is a need for better education and understanding of the procedures for divorce among civil servants. The study also highlights the importance of preventive measures and guidance for civil servants who are considering divorce, as it can affect their work performance and responsibilities. Overall, the implementation of the divorce administration system and procedures in Pelalawan Regency is adequate, but there is room for improvement.